Promoting Social Participation in the Primary Care Field: An Ecological Study on the Potential Reduction of Multimorbidity Prevalence - Ryota Takahashi; Tadao Okada; Kazushige Ide; Taishi Tsuji; Katsunori Kondo (SAGE Publishing, 2024)
Background: No municipal-level study has elucidated the social determinants associated with multimorbidity prevalence (MP). Objective: This article aimed to determine the differences in MP among municipalities and investigate factors associated with such differences through an ecological study of data obtained from a nationwide survey. This article focused on social participation and household income, which are associated with single chronic diseases, such as hypertension. Methods: Study design was a cross sectional study, which used the data from the Japan Gerontological Evaluation Study, a population-based gerontological study among functionally independent older adults aged ≥65 years in Japan. Overall, 152 212 participants from 2016 to 2017 across 91 municipalities were included in the final analysis. Multiple regression analysis was performed with MP as objective variable; social participation or household income were explanatory variables, and education, population density, and health check-ups were adjustment variables. Results: Intermunicipal differences in MP were 28.4% to 43.1% and 23.2% to 38.8% among men and women, respectively. Significant negative correlation was observed between MP and proportion of social participation (non-standardized coefficient [ B ] = −.18 for men and women). A significant positive correlation was noted between MP and equivalent household income of ≤2 million yen in women ( B  = .21). Conclusion: Considerable differences in MP existed among municipalities. Areas with high proportion of social participation showed significantly lower MP. Considering the difficulty in managing multimorbidity within the primary care field and limited evidence on effective interventions, community-level interventions encouraging social participation among older individuals might reduce MP. Primary care physicians should consider a community health approach for multimorbidity.